Proceso de ASC - WRÃ JÎBUSU (MUJER COLIBRI) (2020)
This project will create a musical work that takes the oral tradition discourses of the Embera culture and reimagines them under the aesthetic parameters of the 21st century. Tradition, music, dance, and technology will be integrated, creating a new vision of how Embera culture's beliefs are disseminated. Wẽrã Jîbusu (hummingbird woman) is a mythical musical character of the 21st century, created by the research group. She will be responsible for narrating and singing the stories of her Embera people from her present-day perspective. She is a living, multi-timbral instrument, and her soul in motion brings to life bodies, voices, songs, mystical soundscapes, words, and images. The mission of her songs is to awaken the souls that are unaware of the magic and wisdom of her people.